The perception of time while perceiving dynamic emotional faces - Li, Wang On; Yuen, Kenneth S. (Frontiers in Psychology, 2015)
Emotion plays an essential role in the perception of time such that time is perceived to “fly” when events are enjoyable, while unenjoyable moments are perceived to “drag”. Previous studies have reported a time-drag effect when participants are presented with emotional facial expressions, regardless of the emotion presented. This effect can hardly be explained by induced emotion given the heterogeneous nature of emotional expressions. We conducted two experiments (n=44 & n=39) to examine the cognitive mechanism underlying this effect by presenting dynamic sequences of emotional expressions to participants. Each sequence started with a particular expression, then morphed to another. The presentation of dynamic facial expressions allows a comparison between the time-drag effect of homogeneous pairs of emotional expressions sharing similar valence and arousal to heterogeneous pairs. Sequences of seven durations (400ms, 600ms, 800ms, 1,000ms, 1,200ms, 1,400ms, 1,600ms) were presented to participants, who were asked to judge whether the sequences were closer to 400ms or 1,600ms in a two-alternative forced choice task. The data were then collated according to conditions and fit into cumulative Gaussian curves to estimate the point of subjective equivalence indicating the perceived duration of 1,000ms. Consistent with previous reports, a feeling of “time dragging” is induced regardless of the sequence presented, such that 1,000ms is perceived to be longer than 1,000ms. In addition, dynamic facial expressions exert a greater effect on perceived time drag than static expressions. The effect is most prominent when the dynamics involve an angry face or a change in valence. The significance of this sensitivity is discussed in terms of emotion perception and its evolutionary significance for our attention mechanism.